Synthesis and photooxygenation of homochiral 2-methylpyrrole derivatives of chiral amino alcohols: simple, selective access to chiral bicyclic lactams - Aydogan, F; Demir, AS (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Homochiral 2-methylpyrrole derivatives are synthesized in high yields starting from chiral amino alcohols and 5-chloro-3-pentene-2-one. The photooxygenation of these compounds in the presence of a photosynthesizer furnishes the pyrrolooxazolone structures in high diastereoselectivities. In all of the examples, trans-isomers are formed as the major products. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: SINGLET OXYGEN OXIDATION; DIELS-ALDER REACTIONS; QUATERNARY CARBON-COMPOUNDS; ASYMMETRIC TOTAL SYNTHESIS; ALPHA,BETA-UNSATURATED LACTAMS; FACILE SYNTHESIS; PYRROLES; ACID; CYCLOPROPANES; ANALOGS; Chemistry